NFI and Oct-1 bend the Ad5 origin in the same direction leading to optimal DNA replication - Mysiak, Monika E. (Oxford University Press, 2004)
Two cellular transcription factors, nuclear factor I (NFI) and octamer binding protein (Oct-1), bind simultaneously to their recognition sequences in the Ad5 origin of replication thereby enhancing initiation. Using scanning force microscopy we have previously shown that NFI induces a 60° bend in the origin DNA. Here we demonstrate that Oct-1 induces a 42° bend in the origin DNA. Simultaneous binding of NFI and Oct-1 induces an 82° collective bend suggesting that both bends are oriented towards each other. In functional replication assays we further demonstrate that this extensive DNA bending leads to a synergistic enhancement of DNA replication. We propose that collective DNA bending induced by NFI and Oct-1 facilitates the optimal assembly of the preinitiation complex and plays an important role in the stimulatory mechanism of NFI and Oct-1 in replication.